Tinjauan Pustaka: Pengaruh Obesitas, Resistensi Insulin dan Sindrom Metabolik dengan Fungsi Tiroid - Fala, Arzety Rifda; Windarti, Indri; Jausal, Anisa Nuraisa; Sukohar, Asep (Medula, 2024)
The thyroid gland, located in the neck, is crucial for regulate metabolism, growth, and development by producing hormones like thyroxine (T4) and triiodothyronine (T3). These hormones influence various body functions, including heart rate, temperature control, energy production, and fat metabolism. When the thyroid gland doesn't function properly, it can cause conditions like hypothyroidism or hyperthyroidism. Factors such as obesity, insulin resistance, and metabolic syndrome can disrupt thyroid function. Obesity, characterized by excessive fat accumulation, is a global issue. This study examines how obesity, insulin resistance, and metabolic syndrome affect thyroid function. A review of fourteen relevant articles found that Thyroid Stimulating Hormone (TSH) levels are positively correlated with Body Mass Index (BMI), insulin resistance, and metabolic syndrome. The underlying mechanism is increased levels of leptin and inflammatory cytokines, which affect TSH production and thyroid function through disruption of T3 feedback. The findings indicate that obesity, insulin resistance, and metabolic syndrome lead to increased TSH as a compensatory response. This study highlights the importance of understanding the relationship between these conditions for better prevention and health management.